2016
DOI: 10.1016/j.biortech.2015.10.103
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of digestate from solid anaerobic digesters and dewatered effluent from liquid anaerobic digesters as inocula for solid state anaerobic digestion of yard trimmings

Abstract: To select a proper inoculum for the solid state anaerobic digestion (SS-AD) of yard trimmings, digestate from solid anaerobic digesters and dewatered effluent from liquid anaerobic digesters were compared at substrate-to-inoculum (S/I) ratios from 0.2 to 2 (dry basis), and total solids (TS) contents from 20% to 35%. The highest methane yield of around 244L/kg VSfeed was obtained at an S/I ratio of 0.2 and TS content of 20% for both types of inoculum. The highest volumetric methane productivity was obtained wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 27 publications
(26 reference statements)
2
13
1
Order By: Relevance
“…Additionally, methane yield for DMCS24L in this study was very close to the value (88-113 mL/g VS) documented in a mesophilic SSAD study with switchgrass (Sheets, Ge, and Li 2015). Furthermore, the volumetric methane production gives a good understanding of the utilization efficacy of the reactor volume (Xu et al 2016). The volumetric methane production for treatments DMCS24L and DMCS24S, was 6 and 3 L/L work , respectively (Figure 9).…”
Section: Biogas and Methane Yield And Volumetric Productivitysupporting
confidence: 83%
“…Additionally, methane yield for DMCS24L in this study was very close to the value (88-113 mL/g VS) documented in a mesophilic SSAD study with switchgrass (Sheets, Ge, and Li 2015). Furthermore, the volumetric methane production gives a good understanding of the utilization efficacy of the reactor volume (Xu et al 2016). The volumetric methane production for treatments DMCS24L and DMCS24S, was 6 and 3 L/L work , respectively (Figure 9).…”
Section: Biogas and Methane Yield And Volumetric Productivitysupporting
confidence: 83%
“…A suitable inoculum can improve the biogas yield by increasing the degradation rate, stabilizing the AD, and also shorten the start-up time [72]. Other positive aspects of inoculum are contained N and micronutrients [73]. The micronutrients can enhance the enzyme activity [74] while the extra N can be provided to meet the needs of the methanogens [38].…”
Section: Inoculummentioning
confidence: 99%
“…This is because liquid digestate can provide supplement nitrogen, water, trace elements, and alkalinity to the system [55,56]. Xu et al [57] compared the performance of the dry anaerobic digestion yard trimming of using solid digestate and dewatered effluent from liquid anaerobic digester as inoculum. They found that comparable methane yield and volumetric methane productivities are generated at each F/I ratio (0.2-2, based on TS weight) when conducting the digestion using these two kinds of inoculum, while startup time is reduced using dewatered effluent as inoculum.…”
Section: New Efforts For Operating Dry Anaerobic Digestion Processmentioning
confidence: 99%